Utilizing ATLS® Trauma Management Protocols: The Gold Standard for Safe and Effective Care. - Agron Dogjani; Edvin Selmani; Edmond Zaimi; Kastriot Haxhirexha; Petrit Biberaj; Basri Lenjani; Kastriot Subashi; Ilir Hasmuca; Erjona Zogaj; Amarildo Blloshmi; Klevis Doci (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Approximately 5.8 million people die each year as a result of injuries. Traumatic injury is the leading cause of death under the age of 45 in the U.S. and worldwide. Traumatic injuries represent a significant global health burden, demanding swift and decisive intervention to mitigate morbidity and mortality. The Advanced Trauma Life Support (ATLS) course has emerged as a cornerstone in trauma management, offering healthcare providers a systematic approach to assessment, resuscitation, and definitive care. This article explores the pivotal role of ATLS protocols as the gold standard for safe and effective trauma management.